Effects of ship waves on riverbank erosion in the Mekong delta: A case study in An Giang province - C. N. Thang; T. Hino; C. N X Quang; L G Lam (Lowland Technology International, 2020)
The Mekong Delta is facing with more and more serious riverbank landslides which have a great impact on people's lives, assets and lives, as well as the socio-economic development of local people. There are many causes of riverbank landslides. This study focuses on the causes of riverbank erosion by ship waves. With increasing traffic density, erosion resulting from increasingly serious. In this study, surveying and collecting wave parameters generated by different means were carried out, and the simulation data using laboratory models was also used. Riverbank erosion is assessed through two criteria: the amount of suspended material in the water and the surface erosion of the soil sample. The results show that the ship waves have a significant impact on the erosion of the riverbank and it is possible to predict the level of the erosion by the time.